Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Divission Berbantuan Video Animasi Untuk Meningkatkan Hasil Belajar Matematika Siswa - Dappa Ole, Maria Sriyanti; Ekowati, Christine Khrisnandari; Samo, Damianus D. (Universitas Nusa Cendana, 2024)
This research was motivated by the low learning outcomes of class VIII students at SMP Negeri 2 Amabi Oefeto in mathematics subjects, especially in cartesian coordinates. The aim of this research is to improve the learning outcomes of class VIII students at SMPN 2 Amabi Oefeto through the application of the Student Team Achievement Division (STAD) type of cooperative learning model assited by animated videos on Cartesian coordinate material.The research method used in this research is Classroom Action Research with Kemmis and Mc Taggart model which is carried out in 2 cycles with each cycle having 4 stages, namely 1) planning; 2) implementation; 3) observation; and 4) reflection. Data collection techniques in research are observation, test, and documentation. The data analysis used is qualitative and quantitative descriptive. The results of this study showed that the percentage of classical student learning completeness in cycle I was 62.97%, increasing to 77.78% in cycle II. The value of implementing observations of teacher teaching activities in cycle I and cycle II was 100% and the value of implementing student activities in cycle I 88.46% increased to 100% in cycle II. Thus, it can be concluded that the application of the Student Team Achievement Division (STAD) type of cooperative learning model assisted by animated videos can improve the learning outcomes of class VIII students at SMP Negeri 2 Amabi Oefeto on Cartesian coordinate material.